Consider differentials before diagnosing COVID-19 associated polyradiculitis - Josef Finsterer; Fulvio Alexandre Scorza; Carla Alessandra Scorza; Ana Claudia Fiorini (PAGEPress Publications, 2022)
Evidence is accumulating that SARS-CoV-2 infections and SARS-CoV-2 vaccinations can induce Guillain-Barre syndrome (GBS). More than 400 GBS cases after SARS-CoV-2 infection respectively vaccination have been reported as per the end of 2021. GBS is usually diagnosed according to the Brighton criteria, but also the Besta criteria or Hadden criteria are applied. The diagnosis can be supported by MRI with contrast medium of the cranial or spinal nerves showing enhancing nerve roots. As GBS can be complicated by autonomic dysfunction such as pupillary abnormalities, salivatory dysfunction, reduced heart rate variability, bowel disturbance (constipation, diarrhea), urinary hesitancy, urinary retention, or impotence, it is crucial to investigate GBS patients for autonomic involvement. Before diagnosing GBS various differentials need to be excluded, including neuropathy as a side effect of the anti-SARS-CoV-2 medication, critical ill neuropathy in COVID-19 patients treated on the ICU, and compression neuropathy in COVID-19 patients requiring long-term ventilation.